2020
DOI: 10.1155/2020/8590861
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] CircANXA2 Promotes Myocardial Apoptosis in Myocardial Ischemia‐Reperfusion Injury via Inhibiting miRNA‐133 Expression

Abstract: Objective. This project is aimed at investigating whether CircANXA2 can promote the apoptosis of myocardial cells by inhibiting miR-133 expression and thereby participate in the development of myocardial ischemia-reperfusion injury. Materials and Method. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to detect the expression level of CircANXA2 in H9c2 cells after hypoxia/reoxygenation (H/R) treatment. Evaluation of myocardial injury markers in H9c2 cells was performed using commercial kits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Moreover, the mechanism of RFS-related myocardial injury remains to be elucidated. It has been reported that CK-MB, LDH, and cTnI are markers of myocyte injury (34), and myocardial apoptosis is also a prognostic indicator of myocardial injury (35). Appearance of a reduction in cardiac contractility following a diffuse multifocal inflammatory infiltrate, myocardial fiber disorganization, cardiomyocyte apoptosis, and increased expression of CK-MB, LDH, and cTnI in our study indicated the occurrence of severe myocardial injury induced by SCR.…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, the mechanism of RFS-related myocardial injury remains to be elucidated. It has been reported that CK-MB, LDH, and cTnI are markers of myocyte injury (34), and myocardial apoptosis is also a prognostic indicator of myocardial injury (35). Appearance of a reduction in cardiac contractility following a diffuse multifocal inflammatory infiltrate, myocardial fiber disorganization, cardiomyocyte apoptosis, and increased expression of CK-MB, LDH, and cTnI in our study indicated the occurrence of severe myocardial injury induced by SCR.…”
Section: Discussionsupporting
confidence: 60%
“…Myocardial infarction is a severe disease associated with high mortality, and reestablishing the blood supply to the ischemic myocardial tissue is the most feasible treatment. However, prone to myocardial I/R injury is prone to occur [ 23 ]. Previous studies have shown that myocardial infarction prevention and treatment could target myocardial protective genes or deleterious genes or interfere with pathway gene expression, prompting the balance of protective genes and deleterious gene expression and regulating up- and downstream pathways [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNA is an endogenous, single-stranded, non-coding, small regulatory RNA in a variety of eukaryotic cells ( Diaz et al, 2017 ). Studies have shown that miR-1275, miR-133, miR-148a and miR-324 interfere with the process of MIRI by inhibiting myocardial cell apoptosis, reducing myocardial inflammation, and promoting angiogenesis ( Dai et al, 2020 ; Jiang et al, 2020 ; Zong and Wang, 2020 ). lncRNA is a heterogeneous non-coding RNA that can directly regulate the transcription of target genes and the degradation of proteins ( Ruan et al, 2019 ).…”
Section: Mechanisms Of Myocardial Ischemia–reperfusion Injurymentioning
confidence: 99%